Genetic mapping of loci associated with yield and their components in black common bean (Phaseolus vulgaris L.) - Deivid Lincoln Reche; Maria Celeste Gonçalves‐Vidigal; Pedro Soares Vidigal Filho; Mariana Vaz Bisneta; Giselly Figueiredo Lacanallo; Alessandro A. Brito dos Santos; Abner Pais dos Santos (The Plant Genome)
Abstract The increase in world population linked to climate change leads to the need to develop more productive and more adapted cultivars of food species. Quantitative trait loci (QTLs) mapping is a useful tool although, interaction between genotype and the environment is still a challenge. In this study, we sought to identify QTL related to grain yield and the production components in common beans (Phaseolus vulgaris L.) supported by QTL × environment interaction. Two hundred eight recombinant inbred lines obtained from the Awauna UEM × IPR88 Uirapuru common bean cross were evaluated in 2017, 2018, and 2019 in field conditions under a 15 × 15 triple lattice experimental design. QTL mapping was estimated using genotypic means and a genetic linkage map with 288 single nucleotide polymorphism markers. Five QTLs associated with plant height (PH), number of pods per plant (NPP), first pod height (FPH), 100‐seed weight (SW), and grain yield per plant (GYP) were identified on chromosomes Pv01, Pv04, Pv08, and Pv10. Interestingly, three of these QTLs were co‐localized for more than one trait, where the QTL for PH, NPP, and GYP co‐locate on Pv01, the QTL for PH and FPH co‐locate on Pv04, and the QTL for NPP and SW co‐locate on Pv08. In turn, on Pv10, two distinct QTLs were found for SW. The identification of these QTLs stands out in Brazil since relatively little research is directed at this economically important commercial group. It is noteworthy that the molecular markers found linked to the QTLs must later be validated to be used in a multi‐trait marker‐assisted selection.